CASH WAQF AS A SOLUTION TO OVERCOME DROUGHT IN GUNUNG KIDUL REGENCY IN YOGYAKARTA PROVINCE - Martini Dwi Pusparini; Soya Sobaya; Sri Susanti Agustina Lubis (Tasharruf: Journal Economics and Business of Islam, 2020)
Drought in Gunungkidul Regency is a problem that always occurs almost every year. It has led to humanitarian problems, and requires some appropriate mitigation efforts. Responding to the drought problem, the development of cash waqf in fact is potential to solve the problem. This study aimed at analyzing cash waqf management carried out by ACT Global Waqf in efforts to overcome drought in the Gunungkidul region. This is a field research in which, in this case, the object of research is cash waqf through the Waqf Program of Global well ACT Yogyakarta. Data obtained from eight informants who mastered the object of research, namely Waqf Well of ACT Global Waqf. Based on the results, the cash waqf has been manifested into Waqf Well as determined by Wakif. The efforts to prevent drought by ACT Yogyakarta Global Waqf, especially at three points of waqf wells, greatly helped communities affected by drought. This can be seen from the continued use of the drill well despite drought during the long dry season. The flow of water flowing remains smooth and clean, has not changed since it was built until now. Waqf well is one solution to the community for the freshwater needs, by providing the new water sources by looking for potential water sources and building the infrastructure.